Patogenicidade de Steinernema carpocapsae (Rhabditida: Steinernematidae) ao Cupim de Montículo Cornitermes cumulans (Isoptera: Termitidae) - Rosa, Juliana M. O.; Wilcken, Silvia R. S.; Wilcken, Carlos Frederico [UNESP]; Leite, Luis G. (My University, 2008)
Cornitermes cumulans is a termite species often found in pastures of Brazil, mainly in the most degraded ones. Chemical control has been the most recommended method against this insect pest, but control measures are usually avoided by farmers. Biocontrol of termites with entomopathogenic fungi and possibly with entomopathogenic nematodes have been considered promising techniques, being recommended for use in several countries. This study aimed to evaluate the pathogenicity of Steinernema carpocapsae (an unidentified isolate) against C cumulans castes (workers and soldiers). Three experiments were done, one using Petri dishes, with daily evaluations, and two others in artificial colonies (with workers and soldiers). For one of the experiments in artificial colonies, nematode suspensions (167 and 333 infective juveniles (IJ) per insect) were applied over the food supplied to the termites. For the other experiment, nematode suspensions (133, 267 and 533 IJ per insect) were applied directly over the artificial termite colonies. In these two experiments evaluations were done 1, 5 and 9 days after nematode application. Each dead insect was dissected for nematode verification. S. carpocapsae was highly pathogenic to both castes of C cumulans in all experiments.
Pathogenicity of Steinernema carpocapsae (Rhabditida: Steinernematidae) to the mound termite Cornitermes cumulans (Isoptera: Termitidae)